Agricultural marketing : structural models for price analysis - Vercammen, James (Routledge textbooks in environmental and agricultural economics, 2011)
This book builds on the various theories of commodity price relationships in competitive markets over space, time and form. It also builds on the various theories of commodity price relationships in markets that are non-competitive because processing firms exploit market power, private information distorts commodity bidding, and bargaining is required to establish prices when the marketing transaction involves a single seller and buyer